Initial Impact of the COVID-19 Pandemic on the Employment and Hours of Self-Employed Coupled and Single Workers by Gender and Parental Status - Charlene M. Kalenkoski; Sabrina Wulff Pabilonia (Institute of Labor Economics (IZA), 2020)
This study examines the initial impact of COVID-19 shutdowns on the employment and hours of unincorporated self-employed workers using data from the Current Population Survey. Although the shutdowns decreased employment and hours for all groups, differential effects by gender, couple status, and parental status exist. Coupled women were less likely to be working than coupled men, while single women were more likely to be working than single men. However, fathers of school-age children who remained employed were working reduced hours compared to men without children. Remote work mitigated some of the negative effects on employment and hours.
Keywords: D1; J1; J16; J2; J23; 330; COVID-19; coronovirus; self-employment; entrepreneurship; gender; remote work; working from home; labor supply; child care